Exploring the Mediating Role of Rumination in the Relationship between Objectification and Psychological Burden among Young Females - Kiran, Tayyaba; Bajwa, Ruqia Safdar (Pakistan Journal of Humanities and Social Sciences, 2024)
The current research aimed to examine the impact of sexual and self-objectification on psychological burden among young females. The study also explored the mediating role of rumination in the relationship between sexual and self-objectification and psychological burden. Data was collected from 211 young females by using the purposive sampling technique. Ruminative Response Scale, Depression, Anxiety and Stress Scale 21, Self-Objectification Questionnaire, and Interpersonal Sexual Objectification Scale were used in this study. To analyze the data, SPSS and Process Macro were used. Results revealed that there was a significant impact of self-objectification and sexual objectification on stress, anxiety, and depression in young females. Further, results revealed that rumination plays a mediating role in the relationship between self and sexual objectification and psychological burden. Significant differences were found between unmarried and married females in the scores of sexual objectification but there was no difference in the scores of self-objectification. The results pave the way for further research into the other mechanisms by which objectification leads to psychological burden. Future studies could explore long-term effects, potential resilience factors, and effective interventions.